Centralidade e mobilidade: uma análise do padrão de deslocamento dos pacientes atendidos pelo SUS em Goiás, 2010 - Silva, Cristiano Martins (2014)
The development of the Brazilian urban networks followed the social and economical development of the regions, which at the same time resulted in a differential pattern in the articulation of the same networks, verifying the functional specificities of the urban centers, the polarizing role of the same and the degree of internal and external articulation of each network. In the same way, the regional inequalities reflect in the inequalities of access to health services. In this way, to understand the possibilities of the access of the population of the state of Goiás to public health equipment becomes important disposing about the spatial distribution of the same, because as said by Levy (2002) mobility becomes an important social capital, thus as Villaça (1998) classifies the location in the same way. The spatialization of the health public equipments comes to reflect these differences, as far from the point of view of the resources destined to the municipalities, as the spatial organization of the structures. In this sense, the reflection proposed in this work is to understand the factors of dispersion and the concentration of health and service equipments in the state of Goiás. Especially, to examine about this offering and demand resulting from the aglutination in the core municipalities. For both, it is intended to analyze the behavior of the displacements originated from the hospitalization during the year of the research comparatively to the patient’s local residence and the municipality of hospitalization, intending to identify the flow used by the users of SUS (Unified Health System known as Sistema Único de Saúde). Furthermore, to identify and to analyse a pattern of mobility of the patients in search of hospital and ambulatory treatment. Simultaneously, as support of our analysis, we aim to identify the conditioning factors of the access to health services, as characterizing the users of SUS, having the mobility as fundamental dimension for the existence of a more fair access and equitative of the health services. By the established considerations along this master thesis, it was recognized an excessive concentration of health services offering specialized in few municipalities, with great highlight for Goiânia. This expressive concentration alerts for the risk that the resident population in vast areas of the state needy of these services have major difficulties of access to more complex procedures in the necessary cases.